Meat quality and fatty acid profile in M. longissimus lumborum et thoracis in Prestice Black-Pied pigs fed with linseed diet - NEVRKLA, PAVEL; VÁCLAVKOVÁ, EVA (The Indian Journal of Animal Sciences, 2020)
The study was designed to evaluate the effect of diet with supplementation of linseed scrap fed to Prestice Black-Pied pigs on carcass parameters, meat quality and oxidative stability. We also evaluated the effect of the diet on fatty acid profile in M. longissimus lumborum et thoracis. Barrows (30) of an indigenous breed Prestice Black- Pied pig were included in the experiment. The pigs fed with the linseed diet (L) were characterized by intramuscular fat lower by 1.1% in comparison with the control group (C). Of the saturated fatty acids, C6:0, C8:0 increased while C16:0, C17:0, C18:0 decreased in the experimental group of pigs fed with the L diet when compared to pigs of the C group. Of the monounsaturated fatty acids, a significant decrease of C18:1 n-9 was recorded in the experimental group. The most significant differences were found in polyunsaturated fatty acids (PUFA), where the L group showed an increase in C18:3 n-3, C20:3 n-3, C20:4 n-3 and also C20:5 n-3 a C22:5 n-3. These findings corresponded to higher content of n-3 PUFA and more favourable n-6/n-3 PUFA ratio in the meat of L group against the C group. A higher PUFA/SFA ratio was recorded in the experimental group.